Preparation and characterization of highly stable protic-ionic-liquid membranes - Zakeri, M. (Elsevier Ltd, 2018)
A highly durable proton exchange membranes (PEM)s based on covalently supported ionic liquid (IL) bearing sulfonic acid imidazolium groups were successfully fabricated. The membrane preparation involved radiation induced grafting of 1-vinyl imidazole (1-VIm) onto poly(ethylene-co-tetraflouroethene) (ETFE) film, followed by covalent immobilization of 3-sulfopropyl and subsequent treatment with trifluoromethanesulfonic acid. The ionic conductivity of the supported IL membranes was increased with the increase in the concentration of IL and reached a maximum value of 138 mS cmâ1 in a fully hydrated state with an ion exchange capacity of 4.82 mmol gâ1 that is higher than Nafion with a similar thickness. The membranes displayed excellent chemical and mechanical stability. In addition, the dimensional and thermal stability of supported IL-membranes were significantly higher than commercial Nafion membranes. Â© 2018 Hydrogen Energy Publications LLC